1965
DOI: 10.1063/1.1697153
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Transition-Metal Molybdates. I. Paramagnetic Alpha-MnMoO4

Abstract: Paramagnetic alpha-MnMoO4, the stable phase at STP, is monoclinic with lattice constants a=10.469±0.005, b=9.516±0.005, c=7.143±0.005 Å, and β=106°17′±6′, and space group C2/m. The crystal structure has been solved and refined by a combination of three-dimensional Patterson and Fourier series and by the method of least squares. 1873 independent integrated intensities were measured by PEXRAD; the final agreement factor between measured and calculated structure factors is 0.0574. Two crystallographically indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(64 citation statements)
references
References 19 publications
5
58
0
1
Order By: Relevance
“…Symmetry-equivalent F2o (losin20) observations in each data set were averaged giving the independent reflections (Table 1) used in refinements. The variances 2 2 cr o(Fo ~) taken for S1 data were averages of counting statistics values; those taken for $2 data were the larger of the population and counting statistics (Abrahams & Reddy, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…Symmetry-equivalent F2o (losin20) observations in each data set were averaged giving the independent reflections (Table 1) used in refinements. The variances 2 2 cr o(Fo ~) taken for S1 data were averages of counting statistics values; those taken for $2 data were the larger of the population and counting statistics (Abrahams & Reddy, 1965).…”
Section: Methodsmentioning
confidence: 99%
“…These lattice parameters were obtained using the LeBail extraction technique [9] available in the GSAS program [7]. The C2/m structure has been observed previously in other binary oxides related to CaWO 4 , being its prototype MnMoO 4 [10]. Therefore we have assumed the atomic position parameters of MnMoO 4 to perform the LeBail refinement.…”
mentioning
confidence: 99%
“…A x MoO z types of materials are the special class of inorganic oxide materials which possess mixed state of conductivity (ionic as well as electronic), however, their physical, chemical, and electrochemical properties are largely dependent on the crystal structure (arrangement of the octahedra and tetrahedra in the unit cell). [22,23] Besides, multiple oxidation states of molybdenum ions (Mo 3+ to Mo 6+ ), molybdates of metal or transition metal elements provide robust chemical stability (due to covalent bonding) and excellent ionic conductivity with respect to the electrolyte ions due to the conductive paths paved with metal or transition metal ions. [25,26] Recently, Mai et al [21] demonstrated the use of transition metal molybdates, i.e., CoMoO 4 in nanowire-like morphology as an electrode in pseudocapacitors with a specific capacitance of 62.8 F g −1 (at a current density of 1 A g −1 in a potential window of ΔV = 1 V), and further improved the capacitance to 187 F g −1 (at a current density of 1 A g −1 ) by forming heterostructure of MnMoO 4 /CoMoO 4 nanowires.…”
mentioning
confidence: 99%
“…[14] Polyacid salts of molybdenum, A x MoO z (where A could be a monovalent, divalent, or trivalent metal ion), [15] are interesting host materials for ion insertion applications, particularly in electrochemical energy-storage devices, i.e., batteries [16][17][18] and supercapacitors. [19][20][21] Due to their unique crystal structure (layers of molybdenum oxide octahedra separated by the metal ions), metal-molybdates [22][23][24] become the subject of increasing research interest. A x MoO z types of materials are the special class of inorganic oxide materials which possess mixed state of conductivity (ionic as well as electronic), however, their physical, chemical, and electrochemical properties are largely dependent on the crystal structure (arrangement of the octahedra and tetrahedra in the unit cell).…”
mentioning
confidence: 99%